A peptide mimic of SOCS1 modulates equine peripheral immune cells in vitro and ocular effector functions in vivo: implications for recurrent uveitis - Stafford, Lauren Stewart; Plummer, Caryn E.; Smith, W. Clay; Gibson, Daniel J.; Sharma, Jatin; Vicuna, Valeria; Diakite, Sisse; Larkin, Joseph (Frontiers in Immunology, 2025)
IntroductionRecurrent uveitis (RU), an autoimmune disease, is a leading cause of ocular detriment in humans and horses. Equine and human RU share many similarities including spontaneous disease and aberrant cytokine signaling. Reduced levels of SOCS1, a critical regulator of cytokine signaling, is associated with several autoimmune diseases. Topical administration of SOCS1-KIR, a peptide mimic of SOCS1, was previously correlated to reduced ocular pathologies within ERU patients.MethodsTo further assess the translational potential of a SOCS1 mimetic to treat RU, we assessed peptide-mediated modulation of immune functions in vitro, using equine peripheral blood mononuclear cells (PBMC), and in vivo through topical administration of SOCS1-KIR into the eyes of experimental (non-uveitic) horses. Equine PBMCs from non-uveitic control and ERU horses were cultured with or without SOCS1-KIR pretreatment, followed by 72 hours of mitogen stimulation. Proliferation was assessed using MTT, and cytokine production within cell supernatants was assessed by Luminex. SOCS1-KIR or carrier eye-drops were topically applied to experimental horse eyes twice daily for 21 days, followed by enucleation and isolation of ocular aqueous and vitreous humor. Histology was used to assess peptide treatment safety and localization within treated equine eyes. Cytokine secretion within aqueous humor and vitreous, isolated from experimental equine eyes, was measured by Luminex.ResultsFollowing SOCS1-KIR pretreatment, cell proliferation significantly decreased in control, but not ERU-derived PBMCs. Despite differential regulation of cellular proliferation, SOCS1-KIR significantly reduced TNFα and IL-10 secretion in PHA-stimulated control and ERU equine PBMC. SOCS1-KIR increased PBMC secretion of IL-8. Topically administered SOCS1-KIR was well tolerated. Although SOCS1-KIR was undetectable within the eye, topically treated equine eyes had significant reductions in TNFα and IL-10. Interestingly, we found that while SOCS1-KIR treatment reduced TNFα and IL-10 production in healthy and ERU PBMC, SOCS1-KIR differentially modulated proliferation, IP-10 production, and RANTES within these two groups suggesting possible differences in cell types or activation status.DiscussionTopical administration of a SOCS1 peptide mimic is safe to the equine eye and reduces ERU associated cytokines IL-10 and TNFα serving as potential biomarkers of drug efficacy in a future clinical trial.